IBM z/OS V2R2 : ServerPac - Winnard, Keith; Patwardhan, Nilkanth (IBM redbooks., 2016)
This IBM® Redbooks® publication helps you to become familiar with the technical changes that were introduced into the Serverpac area with IBM z/OS® V2R2. This publication includes the following chapters: - Chapter 1, "ServerPac" on page 1: Provides a summary of the z/OS V2R2 enhancements. - Chapter 2, "Order receive" on page 5: Describes the use of HTTPS to receive your order. - Chapter 3, "Creating a configuration" on page 9: Describes the affect of the SDSF zone change. - Chapter 4, "Variable Panel updates" on page 13: Describes setting up z/OSMF and the SMF option. - Chapter 5, "Modify System Layout option" on page 17: Describes large file system default allocation, enhanced support for file system merge, enhanced support for SMS managed data sets, and new data set view options. - Chapter 6, "Installation job changes" on page 29: Describes changes that were made to the create and submit installation jobs functions, which includes z/OSMF configuration, PFA configuration, KC4z configuration, and SMF logstream setup. This book is one of a series of IBM Redbooks publications that take a modular approach to providing information about the updates that are included with z/OS V2R2. This approach has the following goals: - Provide modular content - Group the technical changes into a topic - Provide a more streamlined way of finding relevant information that is based on the topic We hope you find this approach useful and we welcome your feedback.